A study on the behavior of the dissolved oxygen in the shallow coastal wells of Cuddalore District, Tamilnadu, India - Singaraja, C.; Chidambaram, S.; Prasanna, Mohan; Paramaguru, P.; Johnsonbabu, G.; Thivya, C.; Thilagavathi, R. (Springer Netherlands, 2012)
Dissolved oxygen content in a water column serves as an indicator of pollution and it indirectly indicates the geochemical nature of the water. An attempt has been made in this study to understand the behavior of Dissolved Oxygen (DO) in eleven open wells along the coast of Cuddalore District, Tamilnadu, South India. Observations were made in situ for DO and Electrical Conductivity (EC) depth wise for 24 hours during a full moon period of every two hours. The study indicates that a definite stratification exists in a certain location and mixing trends in some locations. It also shows that there are fluctuations of these values with time and it has a definite relation at specific location. The temporal and the spatial relationships between EC and DO were also used in an attempt to understand the coastal ecosystem in the natural environment.